THE ANALYSIS OF THE FACTORS INFLUENCING DIGITAL PURCHASE DECISIONS ON BUSINESS PLATFORMS IN ECUADOR - Andrade Zamora, Fabrizzio; Celis Torres, Remigio Ecuador; Williams Romero, Verónica (Revista Internacional de Estudios en Ciencias Administrativas STRATEGOS, 2026)
Digital commerce has expanded rapidly in Ecuador, but high traffic does not always translate into completed transactions. This study examined the factors associated with consumers’ digital purchase decisions by combining the Technology Acceptance Model with constructs related to trust, emotion, social influence, and herding behavior. A cross-sectional quantitative design was used. An online questionnaire was completed by 666 Ecuadorian consumers who had purchased online during the previous twelve months. The instrument was reviewed by experts, piloted with 30 participants, and showed high internal consistency (Cronbach’s alpha = 0.94). Descriptive statistics, Pearson correlations, exploratory factor analysis, and multiple linear regression were applied. Three latent factors emerged: trust and social influence, attitude toward the platform, and emotions and herding behavior. Together, they accounted for 76.8% of the variance identified in the factor solution. The regression model explained 76.1% of the variance in purchase intention. Platform trust, ease of use, perceived usefulness, post-purchase satisfaction, and anxiety when disclosing personal data were significant predictors, whereas demographic variables and most social-content indicators did not show direct effects. The findings indicate that Ecuadorian consumers respond most strongly to usable, useful, and trustworthy platforms. Social and emotional cues remain relevant, but much of their influence appears to operate through the broader experience of confidence and platform evaluation.